Durability characteristics of recycled high performance concretes under an aggressive environment (sea water) - Bounouni, Sofiane; Boudina, Tounsia (Technium Social Sciences Journal, 2023)
With the increase of solid construction waste (CSW) due to the acceleration of urbanization in Algeria, many ecological and environmental issues have been raised. Recycling and reuse of construction waste helps to reduce pollution, carbon emissions and preserve resources. Few studies have focused on the durability characteristics of concretes based on fine aggregates recycled from brick and concrete waste. The main purpose of this study is to formulate and analyze the performance of HPC based on waste brick and concrete fines. The substitution of alluvial sand with brick fines, causes the reduction of the heat of hydration and delays the appearance of the thermal flux peaks. while HPC rich in crushed concrete waste increases the heat of hydration. The appearance of heat flux peaks coincides for all mixtures with fines of waste concrete substitution and they will be delayed and prolonged for HPC with sand based on waste brick.